A review of common faults in large-scale heat pumps. (October 2022) - Aguilera, José Joaquín; Meesenburg, Wiebke; Ommen, Torben; Markussen, Wiebke Brix; Poulsen, Jonas Lundsted; Zühlsdorf, Benjamin; Elmegaard, Brian
Abstract: Large-scale heat pumps can contribute towards the decarbonisation of district heating systems and industrial processes. Unidentified faults can have a negative impact on the availability, performance and maintenance costs of heat pump systems. This study provides a description of faults related to the operation of 53 heat pumps based on a vapour compression cycle. Faults were characterized according to potential causes, mitigation or prevention implications as well as detection and diagnosis methods. Faults in the compressor, evaporator and source heat exchanger were more recurrent than in other components of large-scale heat pumps. Overall, the most common faults were fouling of heat exchangers and refrigerant leakage. Faults related to negative impacts like system shutdown, performance reduction and release of refrigerant into the environment, were mainly described to be originated in the compressor. Several directions for future research were identified, which included developing specific fault detection and diagnosis methods for large-scale heat pump applications, proposing methods to detect and diagnose multiple and simultaneous faults, and integrating performance degradation monitoring with fault detection and diagnosis. Highlights: Review of studies that reported faults in large-scale heat pump systems. Description of faults causes, mitigation/prevention, and detection and diagnosis. Most frequent faults found in source heat exchangers, evaporators and compressors. Faults leading to system breakdown were most often caused by compressor failure. Potential future lines of research were outlined.